Biological variation of human aggrecan ARGS neoepitope in synovial fluid and serum in early-stage knee osteoarthritis and after knee injury. Issue 4 (December 2022) - Larsson, Staffan; Lohmander, L. Stefan; Struglics, André
Abstract: Objective: To determine biological variation of the aggrecanase-generated aggrecan ARGS neoepitope in serum (sARGS) and synovial fluid (sfARGS) within and between patients with osteoarthritis (OA) or anterior cruciate ligament (ACL) injury. Design: Matched samples of serum and synovial fluid were available, as parts of clinical trials, from i) 16 subjects with early-stage OA on 8 occasions over 1 year, and ii) 120 subjects with acute ACL injury with samples available from at least 2 of 6 visits over 5 years. We used an in-house immunoassay to quantify ARGS and one-way ANOVA for statistical analyses. Results: Variability in ARGS was higher in synovial fluid than in serum in both patient groups. Subjects with OA had the lowest variability both within and between patients and showed no variation over time in the degree of variability or in the cross-sectional mean, neither in serum nor in synovial fluid. After ACL injury, the concentration and the variability of ARGS was highest immediately after injury, with a subsequent decline both in concentration and in variability with time. In both patient groups there was a positive correlation between sfARGS and sARGS both within and between individuals (correlation coefficients between 0.16 and 0.20). Conclusions: The biological variation of ARGS is lower in serum than in synovial fluid, and lower in OA than after ACL injury. Serum ARGS is a measure of the total release of ARGS aggrecan from the whole body and a poor reflection of the release of ARGS aggrecan within the affected joint.